Comparative study on different types of photovoltaic modules under outdoor operating conditions in Minna, Nigeria - Ezenwora, Joel A.; Oyedum, David O.; Ugwuoke, Paulinus E. (International Journal of Physical Research, 2018)
There is need to always obtain the realistic outdoor performance variables of Photovoltaic (PV) module in a location for efficient PV power system sizing and design. Outdoor performance evaluation was carried out on three types of commercially available silicon PV modules rated 10 W each, using CR1000 software-based Data Acquisition System (DAS). The PV modules under test and meteorological sensors were installed on a metal support structure at the same test plane.The data monitoring was from 08.00 to 18.00 hours each day continuously for a period of one year, from December 2014 to November 2015. Maximum values of module efficiencies of 5.86% and 10.91% for the monocrystalline and polycrystalline modules were respectively recorded at irradiance of 375 W/m2, while the amorphous efficiency peaked at 3.61 % with irradiance of 536.5 W/m2. At 1000 W/m2 the efficiencies reduced to 3.30 %, 6.20 % and 2.25 % as against manufacturer’s specifications of 46 %, 48 % and 33 % for the monocrystalline, polycrystalline and amorphous modules respectively. The maximum power output achieved for the modules at irradiance of 1000 W/m2 were 0.711 W, 1.323 W and 0.652 W for the monocrystalline, polycrystalline and amorphous PV modules, respectively. Accordingly, Module Performance Ratios for the PV modules investigated were 0.07, 0.13 and 0.07, respectively. The rate of variation of module response variables with irradiance and temperature was determined using a linear statistical model given as Y= a + bHg+ c Tmod. The approach performed creditably when compared with measured data.